Incorporation of disinfectants for obtaining dental stone: microbiological and dimensional evaluation - Patrícia Lins Azevedo do Nascimento; Rafael Bezerra Ribeiro; Cícero Romão Gadê-Neto; Alexandre Henrique de Moura Dias
AIM: To assess dimensional change and antimicrobial activity of disinfectants substances incorporated during the dental stone manipulation. MATERIAL AND METHOD: In vivo - microorganisms were collected in alginate molds of 30 volunteers inoculated on BHI agar and incubated at 37 °C for 24 hours. The molds were cast with type IV gypsum, manipulated with saline (G1), 1% sodium hypochlorite (G2) and 4% chlorhexidine (G3), replacing the water. After setting of plaster with 1 hour two collections on models were made. After 24 hours, the readings were performed. The Kruskal-Wallis and Wilcoxon tests with confidence interval of 99% and 95% respectively were used. In vitro - Müeller Hinton agar petri dishes were inoculated with S. mutans (ATCC25175), S. sanguis (ATCC10556) and E. faecalis (ATCC29212), over which were placed steel rings filled with the same substances of the in vivo study. After deposition of gypsum and incubation, halos were measured with a digital caliper and data were submitted to ANOVA and Tukey's test with confidence interval of 95%. Dimensional Change - With a metallic matrix and a perfectly adapted tray, the insertion axis and force used for moulding and obtain 30 specimens in type IV gypsum were standardized, following the same distribution of the study groups in vivo. The specimens were measured by Image Pro Plus software and data were submitted to ANOVA and Tukey's test with confidence interval of 95%. RESULT: Data from the in vivo study demonstrated a significant difference between the mold and each model (p<0.001). In the Wilcoxon test there was no significant difference between groups of models. At the in vitro test, G2 showed greater inhibition zones in all micro-organisms tested compared to G3, but with respect to dimensional changes, there was a significant difference between solutions and metallic standard, where G3 caused less change than G2. CONCLUSION: Chlorhexidine 4% showed to be the most suitable disinfectant.